Control of smectic layering in mono- vs disaccharide-coated polydiacetylenes. Issue 7 (15th July 2022) - Yadav, Shivender; Gowda, Ashwathanarayana; Rao, D. S. Shankar; Prasad, S. Krishna; Jayaraman, N.
ABSTRACT: Amphiphilic sugar-functionalised diacetylene lipids undergo facile self-organisation in the solid state, enabling a photo-initiated polymerisation, leading to the formation of sugar-coated polydiacetylenes. The presence of hydrophilic sugar moiety and the long aliphatic chains promote amphiphilicity-driven mesomorphism in these polymers. Maintaining the lyophilic segment uniform, glycolipids that vary in their sugar constitution are prepared, in order to assess mesomorphic changes with respect to varying sugar segment. Mono- and disaccharides are chosen that allow further to identify the changes in the emerging mesomorphic property with the sugar configurations. Whereas a smectic layering is observed common in these glycolipid polymers, the mesophase temperature range and the structural ordering are observed to vary depending on the sugar segment, as adjudged by optical polarising microscopy, calorimetry and X-ray diffraction assessments. Higher clearing temperatures are seen for disaccharide containing glycolipid polymer, as compared to the monosaccharide containing polymer. Further, in conjunction with energy minimised structures, interdigitised lamellar structure is inferred to the polymers. GRAPHICAL ABSTRACT: uf0001